A method for manufacturing high-toughness FPC

By making coating liquid by modifying resins, silicone resins and other materials, the toughness and thermal conductivity of the flexible circuit board are enhanced, and the problem of insufficient mechanical impact resistance and thermal conductivity of the flexible circuit board is solved, achieving better impact resistance and heat dissipation Effect.

CN115175464BActive Publication Date: 2025-01-14GUANGXI ZHONGPEI PHOTOELECTRIC TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210799998.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-08
Publication Date
2025-01-14
Estimated Expiration
2042-07-08

AI Technical Summary

Technical Problem

The existing flexible circuit boards have poor toughness, poor mechanical impact resistance, and low thermal conductivity, resulting in easy disconnection and overheating.

Method used

The coating solution is made of modified resins, silicone resins, liquid silicone, cellulose mixtures, modified nanosilica and chlorinated polypropylene, and the toughness and thermal conductivity of FPC boards are enhanced through specific mixing and baking processes. .

Benefits of technology

It significantly improves the mechanical impact resistance and thermal conductivity of the FPC board, avoids heat accumulation, and improves the heat dissipation effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115175464B_ABST
    Figure CN115175464B_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of circuit boards, in particular to a method for manufacturing a high-toughness FPC. Aiming at the existing problems of poor mechanical impact resistance and poor thermal conductivity, the following scheme is proposed, which comprises the following steps: the prepared materials include 50 to 70 parts of modified resin, 50 to 60 parts of silicone resin, 30 to 50 parts of liquid silicone, 10 to 15 parts of cellulose mixture, 5 to 10 parts of modified nano silicon dioxide, 1 to 5 parts of chlorinated polypropylene and 1 to 4 parts of coupling agent, and a coating liquid is prepared by using the modified resin, silicone resin, liquid silicone, cellulose mixture, modified nano silicon dioxide, chlorinated polypropylene and coupling agent, and is used for coating on an FPC board, thereby enhancing the toughness of the FPC board, improving the ability of the FPC board to resist mechanical impact, and also improving the thermal conductivity and thermal emissivity of the FPC board, so that the heat of the FPC board can be dissipated outward in time, avoiding heat accumulation and improving the heat dissipation effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of circuit boards, and in particular to a method for manufacturing a high-toughness FPC. Background Art

[0002] The patent with application number CN202010730400.3 discloses a method for manufacturing a flexible circuit board, including the following steps: providing a flexible substrate, a flexible silver paste and a screen printing device, using the screen printing device to print the flexible silver paste on one side of the flexible substrate to form a conductive circuit; providing a drying device, drying the flexible silver paste on the flexible substrate by the drying device, and solidifying the conductive circuit; providing a first injection mold, injection molding a plastic part on the flexible substrate printed with the flexible silver paste by the first injection mold, the conductive circuit formed by the flexible silver paste printed on the flexible substrate is sandwiched between the flexible substrate and the plastic part, and the flexible substrate, flexible silver paste and plastic part are combined to form a flexible circuit board; providing an outer shape cutting device, cutting the outer shape contour of the flexible circuit board by the outer shape cutting device, removing excess waste to form a shaped flexible circuit board.

[0003] However, the manufacturing method of the flexible circuit board also has some problems, such as poor toughness and poor mechanical impact resistance. It is easy to break after multiple impacts, affecting the normal use of the circuit board. In addition, the heat dissipation is limited, the thermal conductivity is low, the heat radiation capacity is poor, and it is not easy to dissipate heat, which can easily cause the circuit board to overheat and burn the internal electronic components. Summary of the invention

[0004] Based on the fact that the background technology has the problems of poor mechanical impact resistance and poor thermal conductivity, the present invention proposes a method for manufacturing a high-toughness FPC.

[0005] The present invention provides a method for manufacturing a high-toughness FPC, comprising the following steps:

[0006] S1: The prepared materials include 50 to 70 parts of modified resin, 50 to 60 parts of silicone resin, 30 to 50 parts of liquid silicone, 10 to 15 parts of cellulose mixture, 5 to 10 parts of modified nano-silica, 1 to 5 parts of chlorinated polypropylene and 1 to 4 parts of coupling agent;

[0007] S2: adding the modified resin, silicone resin and liquid silicone into a water bath device, starting the device for mixing, the water bath temperature is 95° C. to 100° C., stirring for 45 minutes to 60 minutes, thereby obtaining a preliminary mixture;

[0008] S3: pouring the preliminary mixture into a reaction kettle, then adding chlorinated polypropylene and a coupling agent, and controlling the reaction temperature at 120°C to 135°C, stirring the reaction for 15 to 30 minutes, stopping the heating, and slowly adding the modified nano-silicon dioxide and cellulose mixture into the reaction kettle while stirring to continue the reaction, and obtaining a coating liquid after reacting for 30 to 45 minutes;

[0009] S4: Obtain an FPC board, evenly apply the coating liquid on the surface of the FPC board, and then put the coated FPC board into a drying device for baking. The baking temperature is controlled at 75°C to 85°C, and the baking time is 15 minutes to 30 minutes, and finally a high-toughness FPC is obtained.

[0010] Preferably, in S1, the preparation method of the modified resin is: dimer fatty acid and ethanol are evenly mixed in a ratio of 1:10 to prepare a modified solution, and then 20% to 30% of the modified resin of the modified solution is added thereto, and stirred at a temperature of 115°C to 135°C for 1 hour to 2 hours, and the modified resin is obtained after cooling and dehydration.

[0011] Preferably, in S1, the raw material of the modified resin is one of aliphatic glycidyl ether epoxy resin, glycidyl amine epoxy resin, and phenolic epoxy resin, and the epoxy resin is selected from one of the product models E44, E51, E54, and AG80.

[0012] Preferably, in S1, the silicone resin is one of methylphenyl silicone resin, methyl silicone resin, low phenyl methyl silicone resin, silicone resin emulsion, self-drying silicone resin, high temperature silicone resin, epoxy-modified silicone resin, silicone polyester-modified resin, self-drying environmentally friendly silicone resin, environmentally friendly silicone resin, non-stick coating silicone resin, high-gloss silicone resin, benzyl transparent silicone resin, methyl transparent silicone resin, mica bonding silicone resin, polymethyl silicone resin, amino silicone resin, fluorosilicone resin, silicone resin solution, silicone-epoxy resin, silicone polyester resin, solvent-resistant silicone resin, silicone resin adhesive, fluorosilicone resin silicone resin sealant, high temperature resistant methyl silicone resin, self-drying silicone insulating varnish, methyl MQ silicone resin and vinyl MQ silicone resin.

[0013] Preferably, in S1, the method for preparing the cellulose mixture is as follows: cellulose, chitosan and nano zinc dioxide are added to an acetic acid solution and heated and stirred, and then dehydrated after stirring for 30 to 45 minutes to obtain a cellulose mixture.

[0014] Preferably, in S1, the preparation method of the modified nano-silica comprises: mixing a silane coupling agent with nano-silica, and treating the mixture in an ultrasonic container for 30 minutes to 45 minutes, thereby obtaining the modified nano-silica.

[0015] Preferably, in S2, the modified resin and the silicone resin are crushed and ground before being added into the water bath equipment until they can pass through a 50-mesh sieve.

[0016] Preferably, in S2, liquid silica gel is first added, and then the powders of the modified resin and silicone resin are slowly sprinkled in while stirring, and the entire adding process is controlled within 5 minutes to 15 minutes.

[0017] Preferably, in S3, before adding chlorinated polypropylene and the coupling agent, the stirring speed of the reactor is controlled at 100 r / min to 200 r / min, and after adding chlorinated polypropylene and the coupling agent, the stirring speed of the reactor is increased to 500 r / min to 600 r / min. When adding the modified nano-silicon dioxide and the cellulose mixture, the modified nano-silicon dioxide is added first, and then the cellulose mixture is added. During the addition process, the stirring speed of the reactor is reduced to 200 r / min to 300 r / min, and after the addition is completed, the stirring speed of the reactor is increased to 800 r / min to 1200 r / min.

[0018] Preferably, in S4, the FPC board is preheated by baking in a baking oven before being coated with the coating liquid, the baking temperature is controlled at 45° C. to 55° C., and the coating liquid coating process needs to be carried out in a dust-free environment.

[0019] Beneficial effects of the present invention:

[0020] The present invention prepares a coating liquid by using modified resin, silicone resin, liquid silicone, cellulose mixture, modified nano-silica, chlorinated polypropylene and coupling agent, and the coating liquid is used for coating on an FPC board, thereby enhancing the toughness of the FPC board, improving the ability of the FPC board to resist mechanical impact, improving the strength of the FPC board, and also improving the thermal conductivity and thermal emissivity of the FPC board, so that the heat of the FPC board can be dissipated outward in time, avoiding heat accumulation, and improving the heat dissipation effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The working flow chart proposed by the present invention. DETAILED DESCRIPTION

[0022] The present invention will be further explained below in conjunction with specific embodiments.

[0023] Reference Figure 1 , Embodiment 1

[0024] In this embodiment, a method for manufacturing a high-toughness FPC is proposed, comprising the following steps:

[0025] S1: The prepared materials include 68 parts of modified resin, 60 parts of silicone resin, 47 parts of liquid silicone, 15 parts of cellulose mixture, 9 parts of modified nano-silica, 5 parts of chlorinated polypropylene and 4 parts of coupling agent. The preparation method of the modified resin is as follows: dimer fatty acid and ethanol are mixed evenly in a ratio of 1:10 to prepare a modified solution, and then 20% to 30% of the modified resin of the modified solution is added thereto, and stirred at a temperature of 115°C to 135°C for 1 hour to 2 hours, and the modified resin is obtained after cooling and dehydration. The raw material of the modified resin is one of aliphatic glycidyl ether epoxy resin, glycidyl amine epoxy resin, and phenolic epoxy resin. The epoxy resin is selected from one of the product models E44, E51, E54, and AG80. The silicone resin is methylphenyl silicone resin, methyl silicone resin, low phenyl methyl silicone resin, silicone resin emulsion, self-drying silicone resin, high temperature silicone resin, epoxy-modified silicone resin, Silicone polyester modified resin, self-drying environmentally friendly silicone resin, environmentally friendly silicone resin, non-stick coating silicone resin, high-gloss silicone resin, benzyl transparent silicone resin, methyl transparent silicone resin, mica bonding silicone resin, polymethyl silicone resin, amino silicone resin, fluorosilicone resin, silicone resin solution, silicone-epoxy resin, silicone polyester resin, solvent-resistant silicone resin, silicone resin adhesive, fluorosilicone silicone resin sealant, high-temperature resistant methyl silicone resin, self-drying silicone insulating varnish, methyl MQ silicone resin and vinyl MQ silicone resin, preparation method of cellulose mixture; cellulose, chitosan and nano zinc dioxide are added to acetic acid solution for heating and stirring, stirring for 30 minutes to 45 minutes and then dehydrating to obtain a cellulose mixture, preparation method of modified nano silicon dioxide: silane coupling agent and nano silicon dioxide are mixed, and treated in an ultrasonic container for 30 minutes to 45 minutes to obtain modified nano silicon dioxide;

[0026] S2: Add the modified resin, silicone resin and liquid silicone to a water bath, start the equipment to mix, the water bath temperature is 95°C to 100°C, stir for 45 minutes to 60 minutes, and obtain a preliminary mixture. The modified resin and silicone resin are crushed and ground before being added to the water bath until they can pass through a 50-mesh sieve. First add the liquid silicone, and then slowly sprinkle the modified resin and silicone resin powders while stirring. The entire adding process is controlled within 5 minutes to 15 minutes;

[0027] S3: pour the preliminary mixture into a reactor, then add chlorinated polypropylene and a coupling agent, and control the reaction temperature at 120°C to 135°C. After stirring and reacting for 15 to 30 minutes, stop heating, and slowly add the modified nano-silicon dioxide and cellulose mixture while stirring to continue the reaction. After reacting for 30 to 45 minutes, obtain a coating liquid. Before adding chlorinated polypropylene and a coupling agent, the stirring speed of the reactor is controlled at 100 r / min to 200 r / min. After adding chlorinated polypropylene and a coupling agent, the stirring speed of the reactor is increased to 500 r / min to 600 r / min. When adding the modified nano-silicon dioxide and cellulose mixture, the modified nano-silicon dioxide is added first, and then the cellulose mixture is added. During the addition process, the stirring speed of the reactor is reduced to 200 r / min to 300 r / min. After the addition is completed, the stirring speed of the reactor is increased to 800 r / min to 1200 r / min.

[0028] S4: Obtain an FPC board, evenly apply the coating liquid on the surface of the FPC board, and then put the coated FPC board into a drying device for baking. The baking temperature is controlled at 75°C ~ 85°C, and the baking time is 15 minutes ~ 30 minutes. Finally, a high-toughness FPC is obtained. Before applying the coating liquid, the FPC board is preheated in a baking oven. The baking temperature is controlled at 45°C ~ 55°C, and the coating liquid application process needs to be carried out in a dust-free environment.

[0029] Reference Figure 1 , Embodiment 2

[0030] In this embodiment, a method for manufacturing a high-toughness FPC is proposed, comprising the following steps:

[0031] S1: The prepared materials include 62 parts of modified resin, 57 parts of silicone resin, 46 parts of liquid silicone, 14 parts of cellulose mixture, 9 parts of modified nano-silica, 4 parts of chlorinated polypropylene and 4 parts of coupling agent. The preparation method of the modified resin is as follows: dimer fatty acid and ethanol are mixed evenly in a ratio of 1:10 to prepare a modified solution, and then 20% to 30% of the modified resin of the modified solution is added thereto, and stirred at a temperature of 115°C to 135°C for 1 hour to 2 hours, and the modified resin is obtained after cooling and dehydration. The raw material of the modified resin is one of aliphatic glycidyl ether epoxy resin, glycidyl amine epoxy resin, and phenolic epoxy resin. The epoxy resin is selected from one of the product models E44, E51, E54, and AG80. The silicone resin is methylphenyl silicone resin, methyl silicone resin, low phenyl methyl silicone resin, silicone resin emulsion, self-drying silicone resin, high temperature silicone resin, epoxy-modified silicone resin, Silicone polyester modified resin, self-drying environmentally friendly silicone resin, environmentally friendly silicone resin, non-stick coating silicone resin, high-gloss silicone resin, benzyl transparent silicone resin, methyl transparent silicone resin, mica bonding silicone resin, polymethyl silicone resin, amino silicone resin, fluorosilicone resin, silicone resin solution, silicone-epoxy resin, silicone polyester resin, solvent-resistant silicone resin, silicone resin adhesive, fluorosilicone silicone resin sealant, high-temperature resistant methyl silicone resin, self-drying silicone insulating varnish, methyl MQ silicone resin and vinyl MQ silicone resin, preparation method of cellulose mixture; cellulose, chitosan and nano zinc dioxide are added to acetic acid solution for heating and stirring, stirring for 30 minutes to 45 minutes and then dehydrating to obtain a cellulose mixture, preparation method of modified nano silicon dioxide: silane coupling agent and nano silicon dioxide are mixed, and treated in an ultrasonic container for 30 minutes to 45 minutes to obtain modified nano silicon dioxide;

[0032] S2: Add the modified resin, silicone resin and liquid silicone to a water bath, start the equipment to mix, the water bath temperature is 95°C to 100°C, stir for 45 minutes to 60 minutes, and obtain a preliminary mixture. The modified resin and silicone resin are crushed and ground before being added to the water bath until they can pass through a 50-mesh sieve. First add the liquid silicone, and then slowly sprinkle the modified resin and silicone resin powders while stirring. The entire adding process is controlled within 5 minutes to 15 minutes;

[0033] S3: pour the preliminary mixture into a reactor, then add chlorinated polypropylene and a coupling agent, and control the reaction temperature at 120°C to 135°C. After stirring and reacting for 15 to 30 minutes, stop heating, and slowly add the modified nano-silicon dioxide and cellulose mixture while stirring to continue the reaction. After reacting for 30 to 45 minutes, obtain a coating liquid. Before adding chlorinated polypropylene and a coupling agent, the stirring speed of the reactor is controlled at 100 r / min to 200 r / min. After adding chlorinated polypropylene and a coupling agent, the stirring speed of the reactor is increased to 500 r / min to 600 r / min. When adding the modified nano-silicon dioxide and cellulose mixture, the modified nano-silicon dioxide is added first, and then the cellulose mixture is added. During the addition process, the stirring speed of the reactor is reduced to 200 r / min to 300 r / min. After the addition is completed, the stirring speed of the reactor is increased to 800 r / min to 1200 r / min.

[0034] S4: Obtain an FPC board, evenly apply the coating liquid on the surface of the FPC board, and then put the coated FPC board into a drying device for baking. The baking temperature is controlled at 75°C ~ 85°C, and the baking time is 15 minutes ~ 30 minutes. Finally, a high-toughness FPC is obtained. Before applying the coating liquid, the FPC board is preheated in a baking oven. The baking temperature is controlled at 45°C ~ 55°C, and the coating liquid application process needs to be carried out in a dust-free environment.

[0035] Reference Figure 1 , Embodiment 3

[0036] In this embodiment, a method for manufacturing a high-toughness FPC is proposed, comprising the following steps:

[0037] S1: The prepared materials include 58 parts of modified resin, 56 parts of silicone resin, 45 parts of liquid silicone, 13 parts of cellulose mixture, 7 parts of modified nano-silica, 3 parts of chlorinated polypropylene and 3 parts of coupling agent. The preparation method of the modified resin is as follows: dimer fatty acid and ethanol are mixed evenly in a ratio of 1:10 to prepare a modified solution, and then 20% to 30% of the modified resin of the modified solution is added thereto, and stirred at a temperature of 115°C to 135°C for 1 hour to 2 hours, and the modified resin is obtained after cooling and dehydration. The raw material of the modified resin is one of aliphatic glycidyl ether epoxy resin, glycidyl amine epoxy resin, and phenolic epoxy resin. The epoxy resin is selected from one of the product models E44, E51, E54, and AG80. The silicone resin is methylphenyl silicone resin, methyl silicone resin, low phenyl methyl silicone resin, silicone resin emulsion, self-drying silicone resin, high temperature silicone resin, epoxy-modified silicone resin, Silicone polyester modified resin, self-drying environmentally friendly silicone resin, environmentally friendly silicone resin, non-stick coating silicone resin, high-gloss silicone resin, benzyl transparent silicone resin, methyl transparent silicone resin, mica bonding silicone resin, polymethyl silicone resin, amino silicone resin, fluorosilicone resin, silicone resin solution, silicone-epoxy resin, silicone polyester resin, solvent-resistant silicone resin, silicone resin adhesive, fluorosilicone silicone resin sealant, high-temperature resistant methyl silicone resin, self-drying silicone insulating varnish, methyl MQ silicone resin and vinyl MQ silicone resin, preparation method of cellulose mixture; cellulose, chitosan and nano zinc dioxide are added to acetic acid solution for heating and stirring, stirring for 30 minutes to 45 minutes and then dehydrating to obtain a cellulose mixture, preparation method of modified nano silicon dioxide: silane coupling agent and nano silicon dioxide are mixed, and treated in an ultrasonic container for 30 minutes to 45 minutes to obtain modified nano silicon dioxide;

[0038] S2: Add the modified resin, silicone resin and liquid silicone to a water bath, start the equipment to mix, the water bath temperature is 95°C to 100°C, stir for 45 minutes to 60 minutes, and obtain a preliminary mixture. The modified resin and silicone resin are crushed and ground before being added to the water bath until they can pass through a 50-mesh sieve. First add the liquid silicone, and then slowly sprinkle the modified resin and silicone resin powders while stirring. The entire adding process is controlled within 5 minutes to 15 minutes;

[0039] S3: pour the preliminary mixture into a reactor, then add chlorinated polypropylene and a coupling agent, and control the reaction temperature at 120°C to 135°C. After stirring and reacting for 15 to 30 minutes, stop heating, and slowly add the modified nano-silicon dioxide and cellulose mixture while stirring to continue the reaction. After reacting for 30 to 45 minutes, obtain a coating liquid. Before adding chlorinated polypropylene and a coupling agent, the stirring speed of the reactor is controlled at 100 r / min to 200 r / min. After adding chlorinated polypropylene and a coupling agent, the stirring speed of the reactor is increased to 500 r / min to 600 r / min. When adding the modified nano-silicon dioxide and cellulose mixture, the modified nano-silicon dioxide is added first, and then the cellulose mixture is added. During the addition process, the stirring speed of the reactor is reduced to 200 r / min to 300 r / min. After the addition is completed, the stirring speed of the reactor is increased to 800 r / min to 1200 r / min.

[0040] S4: Obtain an FPC board, evenly apply the coating liquid on the surface of the FPC board, and then put the coated FPC board into a drying device for baking. The baking temperature is controlled at 75°C ~ 85°C, and the baking time is 15 minutes ~ 30 minutes. Finally, a high-toughness FPC is obtained. Before applying the coating liquid, the FPC board is preheated in a baking oven. The baking temperature is controlled at 45°C ~ 55°C, and the coating liquid application process needs to be carried out in a dust-free environment.

[0041] Reference Figure 1 , Embodiment 4

[0042] In this embodiment, a method for manufacturing a high-toughness FPC is proposed, comprising the following steps:

[0043] S1: The prepared materials include 55 parts of modified resin, 54 parts of silicone resin, 45 parts of liquid silicone, 14 parts of cellulose mixture, 7 parts of modified nano-silica, 4 parts of chlorinated polypropylene and 3 parts of coupling agent. The preparation method of the modified resin is as follows: dimer fatty acid and ethanol are mixed evenly in a ratio of 1:10 to prepare a modified solution, and then 20% to 30% of the modified resin of the modified solution is added thereto, and stirred at a temperature of 115°C to 135°C for 1 hour to 2 hours, and the modified resin is obtained after cooling and dehydration. The raw material of the modified resin is one of aliphatic glycidyl ether epoxy resin, glycidyl amine epoxy resin, and phenolic epoxy resin. The epoxy resin is selected from one of the product models E44, E51, E54, and AG80. The silicone resin is methylphenyl silicone resin, methyl silicone resin, low phenyl methyl silicone resin, silicone resin emulsion, self-drying silicone resin, high temperature silicone resin, epoxy-modified silicone resin, Silicone polyester modified resin, self-drying environmentally friendly silicone resin, environmentally friendly silicone resin, non-stick coating silicone resin, high-gloss silicone resin, benzyl transparent silicone resin, methyl transparent silicone resin, mica bonding silicone resin, polymethyl silicone resin, amino silicone resin, fluorosilicone resin, silicone resin solution, silicone-epoxy resin, silicone polyester resin, solvent-resistant silicone resin, silicone resin adhesive, fluorosilicone silicone resin sealant, high-temperature resistant methyl silicone resin, self-drying silicone insulating varnish, methyl MQ silicone resin and vinyl MQ silicone resin, preparation method of cellulose mixture; cellulose, chitosan and nano zinc dioxide are added to acetic acid solution for heating and stirring, stirring for 30 minutes to 45 minutes and then dehydrating to obtain a cellulose mixture, preparation method of modified nano silicon dioxide: silane coupling agent and nano silicon dioxide are mixed, and treated in an ultrasonic container for 30 minutes to 45 minutes to obtain modified nano silicon dioxide;

[0044] S2: Add the modified resin, silicone resin and liquid silicone to a water bath, start the equipment to mix, the water bath temperature is 95°C to 100°C, stir for 45 minutes to 60 minutes, and obtain a preliminary mixture. The modified resin and silicone resin are crushed and ground before being added to the water bath until they can pass through a 50-mesh sieve. First add the liquid silicone, and then slowly sprinkle the modified resin and silicone resin powders while stirring. The entire adding process is controlled within 5 minutes to 15 minutes;

[0045] S3: pour the preliminary mixture into a reactor, then add chlorinated polypropylene and a coupling agent, and control the reaction temperature at 120°C to 135°C. After stirring and reacting for 15 to 30 minutes, stop heating, and slowly add the modified nano-silicon dioxide and cellulose mixture while stirring to continue the reaction. After reacting for 30 to 45 minutes, obtain a coating liquid. Before adding chlorinated polypropylene and a coupling agent, the stirring speed of the reactor is controlled at 100 r / min to 200 r / min. After adding chlorinated polypropylene and a coupling agent, the stirring speed of the reactor is increased to 500 r / min to 600 r / min. When adding the modified nano-silicon dioxide and cellulose mixture, the modified nano-silicon dioxide is added first, and then the cellulose mixture is added. During the addition process, the stirring speed of the reactor is reduced to 200 r / min to 300 r / min. After the addition is completed, the stirring speed of the reactor is increased to 800 r / min to 1200 r / min.

[0046] S4: Obtain an FPC board, evenly apply the coating liquid on the surface of the FPC board, and then put the coated FPC board into a drying device for baking. The baking temperature is controlled at 75°C ~ 85°C, and the baking time is 15 minutes ~ 30 minutes. Finally, a high-toughness FPC is obtained. Before applying the coating liquid, the FPC board is preheated in a baking oven. The baking temperature is controlled at 45°C ~ 55°C, and the coating liquid application process needs to be carried out in a dust-free environment.

[0047] Reference Figure 1 Embodiment 5

[0048] In this embodiment, a method for manufacturing a high-toughness FPC is proposed, comprising the following steps:

[0049] S1: The prepared materials include 50 parts of modified resin, 60 parts of silicone resin, 50 parts of liquid silicone, 12 parts of cellulose mixture, 8 parts of modified nano-silica, 3 parts of chlorinated polypropylene and 3 parts of coupling agent. The preparation method of the modified resin is as follows: dimer fatty acid and ethanol are mixed evenly in a ratio of 1:10 to prepare a modified solution, and then 20% to 30% of the modified resin of the modified solution is added thereto, and stirred at a temperature of 115°C to 135°C for 1 hour to 2 hours, and the modified resin is obtained after cooling and dehydration. The raw material of the modified resin is one of aliphatic glycidyl ether epoxy resin, glycidyl amine epoxy resin, and phenolic epoxy resin. The epoxy resin is selected from one of the product models E44, E51, E54, and AG80. The silicone resin is methylphenyl silicone resin, methyl silicone resin, low phenyl methyl silicone resin, silicone resin emulsion, self-drying silicone resin, high temperature silicone resin, epoxy-modified silicone resin, Silicone polyester modified resin, self-drying environmentally friendly silicone resin, environmentally friendly silicone resin, non-stick coating silicone resin, high-gloss silicone resin, benzyl transparent silicone resin, methyl transparent silicone resin, mica bonding silicone resin, polymethyl silicone resin, amino silicone resin, fluorosilicone resin, silicone resin solution, silicone-epoxy resin, silicone polyester resin, solvent-resistant silicone resin, silicone resin adhesive, fluorosilicone silicone resin sealant, high-temperature resistant methyl silicone resin, self-drying silicone insulating varnish, methyl MQ silicone resin and vinyl MQ silicone resin, preparation method of cellulose mixture; cellulose, chitosan and nano zinc dioxide are added to acetic acid solution for heating and stirring, stirring for 30 minutes to 45 minutes and then dehydrating to obtain a cellulose mixture, preparation method of modified nano silicon dioxide: silane coupling agent and nano silicon dioxide are mixed, and treated in an ultrasonic container for 30 minutes to 45 minutes to obtain modified nano silicon dioxide;

[0050] S2: Add the modified resin, silicone resin and liquid silicone to a water bath, start the equipment to mix, the water bath temperature is 95°C to 100°C, stir for 45 minutes to 60 minutes, and obtain a preliminary mixture. The modified resin and silicone resin are crushed and ground before being added to the water bath until they can pass through a 50-mesh sieve. First add the liquid silicone, and then slowly sprinkle the modified resin and silicone resin powders while stirring. The entire adding process is controlled within 5 minutes to 15 minutes;

[0051] S3: pour the preliminary mixture into a reactor, then add chlorinated polypropylene and a coupling agent, and control the reaction temperature at 120°C to 135°C. After stirring and reacting for 15 to 30 minutes, stop heating, and slowly add the modified nano-silicon dioxide and cellulose mixture while stirring to continue the reaction. After reacting for 30 to 45 minutes, obtain a coating liquid. Before adding chlorinated polypropylene and a coupling agent, the stirring speed of the reactor is controlled at 100 r / min to 200 r / min. After adding chlorinated polypropylene and a coupling agent, the stirring speed of the reactor is increased to 500 r / min to 600 r / min. When adding the modified nano-silicon dioxide and cellulose mixture, the modified nano-silicon dioxide is added first, and then the cellulose mixture is added. During the addition process, the stirring speed of the reactor is reduced to 200 r / min to 300 r / min. After the addition is completed, the stirring speed of the reactor is increased to 800 r / min to 1200 r / min.

[0052] S4: Obtain an FPC board, evenly apply the coating liquid on the surface of the FPC board, and then put the coated FPC board into a drying device for baking. The baking temperature is controlled at 75°C ~ 85°C, and the baking time is 15 minutes ~ 30 minutes. Finally, a high-toughness FPC is obtained. Before applying the coating liquid, the FPC board is preheated in a baking oven. The baking temperature is controlled at 45°C ~ 55°C, and the coating liquid application process needs to be carried out in a dust-free environment.

[0053] Comparing the conventional FPC with the FPC obtained in Examples 1 to 5, the FPC obtained in Examples 1 to 5 are shown in the following table:

[0054]

[0055]

[0056] Note: Mechanical impact resistance: From ◎◎◎ to ◎, the impact toughness ranges from good to poor.

[0057] It can be seen from the above table that the mechanical impact resistance, thermal conductivity and thermal emissivity of the FPC prepared by the present invention are significantly improved, and the second embodiment is the best embodiment.

[0058] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for manufacturing a high-toughness FPC, characterized in that: The following steps are involved: S1: The prepared materials include 50 to 70 parts of modified resin, 50 to 60 parts of silicone resin, 30 to 50 parts of liquid silicone, 10 to 15 parts of cellulose mixture, 5 to 10 parts of modified nano-silica, 1 to 5 parts of chlorinated polypropylene and 1 to 4 parts of coupling agent; S2: adding the modified resin, silicone resin and liquid silicone into a water bath device, starting the device for mixing, the water bath temperature is 95° C. to 100° C., stirring for 45 minutes to 60 minutes, thereby obtaining a preliminary mixture; S3: pouring the preliminary mixture into a reaction kettle, then adding chlorinated polypropylene and a coupling agent, and controlling the reaction temperature at 120°C to 135°C, stirring the reaction for 15 to 30 minutes, stopping the heating, and slowly adding the modified nano-silicon dioxide and cellulose mixture into the reaction kettle while stirring to continue the reaction, and obtaining a coating liquid after reacting for 30 to 45 minutes; S4: Obtain an FPC board, evenly apply the coating liquid on the surface of the FPC board, and then put the coated FPC board into a drying device for baking. The baking temperature is controlled at 75°C to 85°C, and the baking time is 15 minutes to 30 minutes, and finally a high-toughness FPC is obtained.

2. The method for manufacturing a high-toughness FPC according to claim 1, characterized in that: In S1, the preparation method of the modified resin is as follows: dimer fatty acid and ethanol are uniformly mixed in a ratio of 1:10 to prepare a modified solution, and then 20% to 30% of the modified resin of the modified solution is added thereto, and stirred at a temperature of 115° C. to 135° C. for 1 hour to 2 hours, and the modified resin is obtained after cooling and dehydration.

3. The method for manufacturing a high-toughness FPC according to claim 1, characterized in that: In S1, the raw material of the modified resin is one of aliphatic glycidyl ether epoxy resin, glycidyl amine epoxy resin, and phenolic epoxy resin, and the epoxy resin is selected from one of the product models E44, E51, E54, and AG80.

4. The method for manufacturing a high-toughness FPC according to claim 1, characterized in that: In S1, the silicone resin is one of methylphenyl silicone resin, methyl silicone resin, low-phenylmethyl silicone resin, silicone resin emulsion, self-drying silicone resin, high-temperature silicone resin, epoxy-modified silicone resin, silicone polyester-modified resin, self-drying environmentally friendly silicone resin, environmentally friendly silicone resin, non-stick coating silicone resin, high-gloss silicone resin, benzyl transparent silicone resin, methyl transparent silicone resin, mica bonding silicone resin, polymethyl silicone resin, amino silicone resin, fluorosilicone resin, silicone resin solution, silicone-epoxy resin, silicone polyester resin, solvent-resistant silicone resin, silicone resin adhesive, fluorosilicone resin silicone resin sealant, high-temperature resistant methyl silicone resin, self-drying silicone insulating varnish, methyl MQ silicone resin and vinyl MQ silicone resin.

5. The method for manufacturing a high-toughness FPC according to claim 1, characterized in that: In S1, a method for preparing a cellulose mixture is provided; cellulose, chitosan and nano zinc dioxide are added to an acetic acid solution and heated and stirred, and then dehydrated after stirring for 30 to 45 minutes to obtain a cellulose mixture.

6. The method for manufacturing a high-toughness FPC according to claim 1, characterized in that: In S1, the preparation method of modified nano-silica is as follows: a silane coupling agent is mixed with nano-silica, and the mixture is treated in an ultrasonic container for 30 minutes to 45 minutes, thereby obtaining modified nano-silica.

7. The method for manufacturing a high-toughness FPC according to claim 1, characterized in that: In S2, the modified resin and the silicone resin are crushed and ground before being added into the water bath until they can pass through a 50-mesh sieve.

8. The method for manufacturing a high-toughness FPC according to claim 1, characterized in that: In S2, liquid silicone is first added, and then the modified resin and silicone resin powders are slowly sprinkled in while stirring. The entire adding process is controlled within 5 minutes to 15 minutes.

9. The method for manufacturing a high-toughness FPC according to claim 1, characterized in that: In S3, before adding chlorinated polypropylene and coupling agent, the stirring speed of the reactor is controlled at 100r / min~200r / min. After adding chlorinated polypropylene and coupling agent, the stirring speed of the reactor is increased to 500r / min~600r / min. When adding modified nano-silica and cellulose mixture, modified nano-silica is added first, and then the cellulose mixture is added. During the addition process, the stirring speed of the reactor is reduced to 200r / min~300r / min. After the addition is completed, the stirring speed of the reactor is increased to 800r / min~1200r / min.

10. The method for manufacturing a high-toughness FPC according to claim 1, characterized in that: In S4, the FPC board is preheated by baking in a baking oven before being coated with the coating liquid, the baking temperature is controlled at 45° C. to 55° C., and the coating liquid coating process needs to be carried out in a dust-free environment.

Citation Information

Patent Citations

  • Manufacturing method of flexible circuit board

    CN111867265A

  • A surface protection method for flexible printed circuit boards

    CN102271466A

  • Toughening type epoxy resin composition for flexible printed circuit board

    CN106978119A